Analisis Ketahanan Hidup Pada Penderita Kanker Serviks Menggunakan Regresi Cox Proportional Hazard - Ummi Hafildah; Ria Dhea Layla Nur Karisma (Jurnal Riset Mahasiswa Matematika, 2022)
Survival analysis is a statistical method used to analyze data with time until the occurrence of a certain event which is commonly referred to as "failure". One of the objectives of survival analysis is to determine the effect of predictor variables on survival time. The purpose of this study was to determine the regression model and determine the hazard ratio of each factor that is thought to affect the survival of cervical cancer patients. The results of this study showed that the factors that influence patients with cervical cancer in their survival are stage II and stage III variables (the patient’s stage), complications, and a history of pregnancy (who have children 0-2).